Potensi Khamir sebagai Agens Pengendalian Hayati Colletotrichum capsici, Cendawan Penyebab Antraknosa pada Buah Cabai - Okky Setyawati Dharmaputra; Lisdar I. Sudirman; Maria M. Misnawati (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2016)
ABSTRACTAntrachnose on chilli fruit caused by Colletotrichum capsici can reduce yield and quality of chilli fruit. Biological control agent can be used as an alternative to control C. capsici. Yeast is one of biological control agent which is potential to control the pathogen. This study was aimed at testing antagonistic potential of yeast on fruits and vegetables against C. capsici. Twenty two yeast isolates were isolated from banana, rambutan, red chilli, tomato, and eggplant fruits. Screening for antagonistic yeast using well test showed that 5 isolates of yeast (CMM-1, CMM-3, CMM-4, TMM-1, and EMM-11) completely inhibited the growth of C. capsici. Based on the result of biocontrol assay of the pathogen in vivo, four yeast isolates (CMM-3, CMM-4, TMM-1, and EMM-11) completely inhibited C. capsici in vivo. Identification using morphological and molecular characteristics showed that these four yeast isolates were Issatchenkia orientalis.Keywords: antagonistic yeast, antrachnose, biocontrol, Issatchenkia orientalis ABSTRAK Antraknosa pada buah cabai yang disebabkan oleh Colletotrichum capsici dapat menyebabkan penurunan produksi dan kualitas buah cabai. Penggunaan agens pengendalian hayati dapat menjadi salah satu alternatif untuk mengendalikan C. capsici. Khamir merupakan salah satu agens pengendalian hayati yang berpotensi mengendalikan C. capsici. Penelitian ini bertujuan menguji potensi antagonistik khamir pada buah-buahan dan sayuran terhadap C. capsici. Sebanyak 22 isolat khamir diisolasi dari buah rambutan, pisang, cabai merah besar, tomat, dan terung ungu. Seleksi khamir antagonis menggunakan uji sumur diperoleh sebanyak 5 isolat khamir, yaitu isolat CMM-1, CMM-3, CMM-4, TMM-1, dan EMM-11 menghambat total pertumbuhan C. capsici. Isolat CMM-3, CMM-4, TMM-1, dan EMM-11 menghambat total pertumbuhan C. capsici in vivo. Berdasarkan hasil identifikasi secara morfologi dan molekuler, isolat CMM-3, CMM-4, TMM-1, dan EMM-11 adalah Issatchenkia orientalis.Kata kunci: antraknosa, Issatchenkia orientalis, khamir antagonis, pengendalian hayati